Student Knowledge Regarding The Implementation Of Covid-19 Health Protocol - Ernawaty Siagian (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: Transmission of COVID-19 in the community was caused by the lack of knowledge regarding the virus transmission preventions. This is a trigger for people not to comply with health protocols such as wearing masks, diligently washing hands properly and maintaining physical distance. Objectives: This study aims to determine the relationship of knowledge to the implementation of the COVID-19 health protocol in students. Methods: This study uses the descriptive analytic method with a qualitative approach. The subjects of this study were junior high school students aged 13-15 years totaling 89 people who were selected by purposive sampling technique. Data were analyzed univariately using frequency and presentation. Bivariate analysis with Pearson correlation. Results: The analysis shows that there is no significant relationship between online games and interest in learning with ap value of 0.207 > 0.05 and there is a significant relationship between age and class level on the implementation of the COVID-19 health protocol with a sig value of 0.018 (p value > 0.05 Conclusion: Overall, most of the respondents have good knowledge, positive attitude, and good practices toward preventing COVID-19. where the student's knowledge becomes a reference for students to behave and behave according to health protocols.